2003
DOI: 10.1016/s0002-9440(10)63641-3
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Significance of Cathepsin S Expression in Human Astrocytomas

Abstract: Early local invasion by astrocytoma cells results in tumor recurrence even after apparent total surgical resection, leading to the poor prognosis associated with malignant astrocytomas. Proteolytic enzymes have been implicated in facilitating tumor cell invasion and the current study was designed to characterize the expression of the cysteine proteinase cathepsin S (CatS) in astrocytomas and examine its potential role in invasion. Immunohistochemical analysis of biopsies demonstrated that CatS was expressed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 41 publications
(36 reference statements)
2
75
0
1
Order By: Relevance
“…overexpression of cathepsin S has been reported in several types of human cancer in the lung (7), prostate (8), brain (9) and pancreas (4). In the present study, we showed for the first time that cat S was not expressed or expressed at a very low basal level in the hepatocytes of normal human livers, but was greatly elevated in cancerous hepatocytes in a significant percentage of human hepatocellular carcinoma livers.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…overexpression of cathepsin S has been reported in several types of human cancer in the lung (7), prostate (8), brain (9) and pancreas (4). In the present study, we showed for the first time that cat S was not expressed or expressed at a very low basal level in the hepatocytes of normal human livers, but was greatly elevated in cancerous hepatocytes in a significant percentage of human hepatocellular carcinoma livers.…”
Section: Discussionsupporting
confidence: 56%
“…in addition, cat S was found to be overexpressed in endothelial cells in a late-stage liver tumor in a genetic mouse model of Hcc (6), suggesting a role for cat S in angiogenesis and cancer metastasis. in humans, cat S has been implicated in several types of cancers, including lung cancer (7), prostate cancer (8) and astrocytoma (9). Based on this new evidence, cat S was proposed as a potential drug target for cancer therapy (3,10).…”
Section: ) (Vasiljeva Et Al)mentioning
confidence: 99%
“…The expression of Cat S together with Cat B was found in neoplastic prostatic cells from pre-invasive to invasive and clinically detectable stage 8 . Cat S is expressed in astrocytoma derived from brain tumor cell cultures, but not in those cells from normal astrocytes, oligodendrocytes, neurons and endothelial cells 9 . The highest levels of Cat S activity were also found in grade IV tumors among 59 astrocytoma biopsies 10 .…”
Section: Introductionmentioning
confidence: 90%
“…The invasive and pro-angiogenic effects in preclinical and clinical evaluation were blocked by antibody Fsn0503 against Cat S 6 . The invasive behavior in U251MG glioblastoma cells was disrupted by a peptidic, irreversible Cat S inhibitor, 4-morpholineureaLeu-HomoPhe-vinylsulphone 9 . These studies indicate that Cat S correlates with cancer migration and invasion and is a potential target for anti-migration and anti-invasive therapy 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…In vitro Invasion Assays In vitro invasion assays were done as described previously (18). Briefly, cells were incubated in the presence of predetermined concentrations of rCatSPP, rCatSPP-Fc, or appropriate controls, and invasion plates were incubated at 37jC and 5% CO 2 for 24 h. Noninvaded cells were removed and invaded cells were fixed in Carnoy's fixative for 15 min.…”
Section: Cloning Of Rcatspp and Rcatspp-fcmentioning
confidence: 99%